If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2s + -2) + -6 = -3(7s + 3) + -4 Reorder the terms: -3(-2 + 2s) + -6 = -3(7s + 3) + -4 (-2 * -3 + 2s * -3) + -6 = -3(7s + 3) + -4 (6 + -6s) + -6 = -3(7s + 3) + -4 Reorder the terms: 6 + -6 + -6s = -3(7s + 3) + -4 Combine like terms: 6 + -6 = 0 0 + -6s = -3(7s + 3) + -4 -6s = -3(7s + 3) + -4 Reorder the terms: -6s = -3(3 + 7s) + -4 -6s = (3 * -3 + 7s * -3) + -4 -6s = (-9 + -21s) + -4 Reorder the terms: -6s = -9 + -4 + -21s Combine like terms: -9 + -4 = -13 -6s = -13 + -21s Solving -6s = -13 + -21s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '21s' to each side of the equation. -6s + 21s = -13 + -21s + 21s Combine like terms: -6s + 21s = 15s 15s = -13 + -21s + 21s Combine like terms: -21s + 21s = 0 15s = -13 + 0 15s = -13 Divide each side by '15'. s = -0.8666666667 Simplifying s = -0.8666666667
| x^3+x^2-42x-291=0 | | 4x+5y+8=0 | | p=3.04+.077y | | 7381=-5/x^6 | | (6x-1)(9x+6)=0 | | x^2-3x-2x-6=0 | | (2x+9)(x-5)=50 | | 2c^2+9z-2=0 | | 7x^2+12x-9=0 | | y=-.13+24.04 | | 4+2+(x-3)=8x+6 | | 7/x=147 | | 0.07x=3.01 | | 15y+28-2(9y+2)= | | 9y+2= | | 7-(3/4)(3/4) | | 15y+28-9y+2=9y+2 | | 4-2(x+3)=3(x+5) | | tanx(sinx+1)=0 | | h=4t | | 8x=5t-62 | | 3y=9x-18 | | d=t+9 | | -8y+9x=-5 | | 467000/192000*100 | | −18/3 | | 4(2x+-3)=4x+3+20+3x | | -7x-4=-60 | | 23+17x+1=22x+4 | | x+70=36 | | 18x^3-9x^2-2x= | | 22x+4-17x+1=32 |